Mitochondrial HIGD1A inhibits hepatitis B virus transcription and replication through the cellular PNKD‐NF‐κB‐NR2F1 nexus. Issue 4 (21st April 2023) - Xie, Zhanglian; Shen, Sheng; Huang, Kuiyuan; Wang, Weibin; Liu, Ziying; Zhang, Haixing; Lu, Mengji; Sun, Jian; Hou, Jinlin; Liu, Hongyan; Guo, Haitao; Zhang, Xiaoyong
Abstract: Hepatitis B Virus (HBV) replication has been reported to be restricted by the intrahepatic host restriction factors and antiviral signaling pathways. The intracellular mechanisms underlying the significant viremia difference among different phases of the natural history chronic HBV infection remain elusive. We herein report that the hypoxia‐induced gene domain protein‐1a (HIGD1A) was highly expressed in the liver of inactive HBV carriers with low viremia. Ectopic expression of HIGD1A in hepatocyte‐derived cells significantly inhibited HBV transcription and replication in a dose‐dependent manner, while silence of HIGD1A promoted HBV gene expression and replication. Similar results were also observed in both de novo HBV‐infected cell culture model and HBV persistence mouse model. Mechanistically, HIGD1A is located on the mitochondrial inner membrane and activates nuclear factor kappa B (NF‐κB) signaling pathway through binding to paroxysmal nonkinesigenic dyskinesia (PNKD), which further enhances the expression of a transcription factor NR2F1 to inhibit HBV transcription and replication. Consistently, knockdown of PNKD or NR2F1 and blockage of NF‐κB signaling pathway abrogated the inhibitory effect of HIGD1A on HBV replication. Mitochondrial HIGD1A exploits the PNKD‐NF‐κB‐NR2F1 nexus to act as a host restriction factor of HBV infection. Our study thus shed new lights on the regulation of HBV by hypoxia‐related genes and related antiviral strategies.